Can ultrasound elastography identify mass-like focal fatty change (FFC) from liver mass?. Issue 39 (September 2017) - Qiu, Tingting; Ling, Wenwu; Li, Jiawu; Lu, Qiang; Lu, Changli; Li, Xiaomin; Zhu, Cairong; Luo, Yan
Abstract : Abstract: Focal fatty change (FFC) may mimic liver mass on conventional B-mode ultrasound. Clinical differentiation of mass-like FFC and liver mass is important due to different clinical interventions. Contrast-enhanced imaging (CEI) or biopsy is reliable for this differentiation, but is expensive and invasive. This study aimed to explore utilities of ultrasound elastography for this differentiation. This study enrolled 79 patients with focal liver lesions (FLLs), of which 26 were mass-like FFC confirmed by at least 2 CEI modalities. The other 53 were liver masses, confirmed by pathology (n = 28) or at least 2 CEI modalities (n = 25). Lesion stiffness value (SV), absolute stiffness difference (ASD), and stiffness ratio (SR) of lesion to background were obtained using point shear-wave elastography (pSWE) and compared between FFC group and liver mass group. The performance of SV, ASD, and SR for identifying FFC from liver mass was evaluated. SV was 5.6 ± 2.4 versus 16 ± 12 kPa, ASD was 2.0 ± 1.9 versus 11 ± 12 kPa, and SR was 1.4 ± 0.6 versus 3.0 ± 1.9 for FFC and liver mass group, respectively ( P < .0001). The area under the receiver operating characteristic curve of SV, ASD, and SR for discriminating mass-like FFC and liver mass was 0.840, 0.842, and 0.791, respectively ( P < .05). Particularly, with cut-off ASD < 1.0 kPa, positive predictive value was 100%, specificity was 100%, and accuracy was 82% for diagnosing FFC. pSWE may be a potential useful modality for identifying mass-like FFC from liver mass, which might help reduce the necessity for further CEI or biopsy for diagnosing mass-like FFC.